Phylogenetic study of the tribe Potentilleae (Rosaceae), with further insight into the disintegration of Sibbaldia. Issue 3 (20th March 2017) - Feng, Tao; Moore, Michael J.; Yan, Min‐Hui; Sun, Yan‐Xia; Zhang, Hua‐Jie; Meng, Ai‐Ping; Li, Xiao‐Dong; Jian, Shu‐Guang; Li, Jian‐Qiang; Wang, Heng‐Chang
Abstract: Potentilleae, one of 10 tribes of the Rosaceae, are mainly distributed in alpine regions of the Northern Hemisphere. The taxonomy of Potentilleae has been challenging due to extensive hybridization, polyploidization, and/or apomixis characterizing several genera of Potentilleae, such as Alchemilla, Argentina, and Potentilla . To help clarify relationships within Potentilleae, a phylogenetic analysis of the tribe with an emphasis on the polyphyletic genus Sibbaldia was carried out using nuclear ribosomal internal and external transcribed spacer regions and the plastid trnL‐F and trnS‐G spacer regions. In agreement with previous phylogenetic analyses, three major clades were identified in the present study: the subtribe Fragariinae, the genera Argentina, and Potentilla . The 15 species of Sibbaldia were recovered in five distinct clades: three in subtribe Fragariinae, one in Argentina, and the last in Potentilla . The recently established genus Chamaecallis, comprising a single species formerly treated in Sibbaldia that has intermediate floral character states with respect to Fragariinae and Potentilla, was recovered as sister to Drymocallis . Morphological character state reconstruction indicated that a reduction in the number of stamens (≤10) is a derived character state that has arisen multiple times in Potentilleae. Molecular dating analyses agreed with previously published estimates and suggested that crown group Potentilleae arose in the Middle to Late Eocene, with most generic‐level divergences occurring in the Oligocene and Miocene.